Identification of factors affecting competitive tension in the domestic air transport market in Turkey - Mehmet Yasar; Ender Gerede (International Journal of Management and Economics, 2020)
Competitive tension refers to pressure that is considered to exist among firms operating in a competitive market and that forces them to take competitive action against each other. An imaginary upper limit of competitive tension symbolizes the difference between whether to take competitive action or not. The antecedents of competitive tension are examined in this study. Within this scope, market commonality and resource similarity are the variables studied as components of competitor analysis; market concentration that provides clues for the competitive structure of competed markets; and finally, competitive asymmetry, presuming that the competition among the companies is not equal and rivals do not consider each other at the same level as competing firms, were taken as primary variables of competitive tension. In order to test whether these variables have an effect on competitive tension among airlines, airlines operating in the domestic air transport market in Turkey were examined in this study. The perceived competitive tension that was detected as a result of regression analyses was studied on three different dimensions, namely, internal tension, external tension, and total tension, and each dimension was analyzed as a different model. The findings of the study revealed that market commonality and market concentration have a significant effect on competitive tension. These effects were found to be positive for market commonality and negative for market concentration. Resource similarity and competitive asymmetry were found to have no significant effect.
Keywords: L13; L25; L93; 650; strategic management; competition; competitive dynamics; perceived competitive tension; rival analysis